Impulse Buying Behaviour of Womankind: Triggered By Their Mood and Lifestyle - Abadi, Rahmat Riwayat; Abadi, Ridfan Rifadly; Mustafa, Muhammad Yushar; Aslam, Annisa Paramaswary (PT. Maju Malaqbi Makkarana, 2023)
As it expands, modern retailing must always be able to adapt to the lifestyle trends in society and understand the aspects that influence consumers' shopping behavior by implementing a unique store concept. Shopping has become a habit for some people, including women, who are becoming more numerous and financially empowered. This research was conducted to test and analyze the effect of shopping lifestyle and in-store displays on impulse buying among female consumers who use and buy branded fashion products at the UNIQLO store in Makassar City. The research sample consisted of 100 respondents using a non-probability sampling technique with a purposive method. The data collection method used was a questionnaire with a Likert scale. The data analysis method used was multiple linear regression analysis, which was processed using SPSS version 25. The results showed that shopping lifestyle had a significant effect on impulse buying and in-store displays had a significant effect on impulse buying.